Traditional Chinese Medicine (TCM) research articles unpacked: a systemic functional linguistics (SFL) elemental genre approach - Lin Zhao; Pramoolsook Issra (Cogent Arts & Humanities)
Over the past two decades, extensive research has been conducted on the rhetorical structure of research articles (RAs) from the English for Specific Purposes (ESP) genre approach. However, RA configuration from the Systemic Functional Linguistic (SFL) genre perspective remains under-investigated, particularly in the Traditional Chinese Medicine (TCM) field. This study aimed to examine the deployment of SFL elemental genres to construct the TCM RAs. To this end, 40 empirical articles published from 2020 to 2021 were selected from five high-impact TCM journals for the analysis. The findings showed that report, recount, argument, and explanation were employed to construct the TCM RAs. Under these broad genre families, 13 elemental genres were identified, for instance, descriptive report, procedural recount, exposition and factorial explanation. Regarding the frequency, report and recount played a major role in configuring the TCM RAs whereas argument and explanation played a supplementary role. Moreover, the ESP genre held that the macro-structure of RA is shaped like an hourglass, which was also attested by the present SFL elemental genres in terms of the generic complexity. Such deconstruction of a macrogenre into elemental genres serving as building blocks of text promises pedagogical implications for English for Academic Purposes (EAP) teachers and graduate students.